The Role of Independent Curriculum and Character Education in the Family Space of Generation Z Facing Social Dynamics - Paulus Satyo Istandar Tan (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
The Independent Curriculum and character education in the family room have not fully equipped Generation Z to face the rapidly changing social dynamics. In addition, there is still a gap between the role of the family and the implementation of the curriculum in forming adaptive, critical, and integrity-based characters in the younger generation. This study aims to examine the influence of the Independent Curriculum (X1), character education (X2), and the family room (Z) on Generation Z's ability to face social dynamics (Y). This research problem focuses on how these three factors influence the character formation and social behavior of Generation Z in the context of rapid social change. This study uses a quantitative approach with Smart PLS 4.0 analysis. The research sample consisted of 212 junior high and high school students, who were selected through a questionnaire with a Likert scale. The results of the analysis show that the independent curriculum has a significant effect on social dynamics, while the effect of character education is not significant. The family room also has a positive influence on social dynamics, although its contribution is smaller compared to the Independent Curriculum. This study suggests that character education needs to be supported by a more adaptive curriculum to maximize its influence.